Damage identification method using harmonic excitation force considering both modelling and measurement errors. - Furukawa, Aiko
A method of structural damage identification using harmonic excitation force is presented. It considers the effects of both measurement and modelling errors in the baseline finite element model. Damage that accompanies changes in structural parameters can be estimated for a damaged structure from the change between measured vibration responses and ones calculated from the analytical model of the intact structure. In practice, modelling errors exist in the analytical model due to material and geometric uncertainties and a reduction in the degrees of freedom as well as measurement errors, making identification difficult. To surmount these problems, bootstrap hypothesis testing, which enables statistical judgment without information about these errors, was introduced. The method was validated by numerical simulation using a three dimensional frame structure and real vibration data for a three storey steel frame structure.
Keywords: Structural damage identification; Harmonic excitation; Frequency response function; Modelling errors; Measurement errors; Bootstrap hypothesis testing